Organizational Challenges for Schools in Rural Municipalities: Cross-National Comparisons in a Nordic Context - Tommy Lind; Olof Stjernstrom (Journal of Research in Rural Education, 2015)
In this study, the spatial structure of primary schools and alternative organizational frameworks are studied in a number of rural municipalities in the northern parts of Norway, Sweden, and Finland. The aim of the study is to investigate how the spatial structure of schools has changed between the years 2008 and 2013 in these municipalities, what strategies the municipalities have developed to adapt their schools to changing conditions, and what constraints there are to apply the strategies at the local level. To answer these questions, semi-structured interviews with municipal representatives were conducted. Substantial changes to the spatial structure of school organizations through closures and mergers can be observed. The overall strategy for the future in all three national settings is a spatial structure with well equipped and well staffed schools in municipal centers and as few small village schools as possible, using information and communication technology (ICT) as a distance-bridging technology. The constraints to applying these strategies are on three different spatial levels. At the state level, the state places constraints regarding what municipalities and schools can and cannot do. At the municipal level, local politicians do not want to close schools for fear of losing the next election. At the community level, the constraints mainly lie in the resistance and strong social capital of the inhabitants who are focused on keeping their schools open irrespective of per capita costs.